To commit a crime while carrying weapons - Rodríguez Collao, Luis; Antivil Valencia, Álvaro (Revista de Estudios de la Justicia, 2024)
This paper deals with the aggravating circumstance of criminal liability provided for in article 12 number 20 of the Chilean Criminal Code, consisting of executing a crime while carrying a weapon. The analysis includes the determination of the meaning and scope of this aggravating circumstance, as well as its nature, its basis and the relationships that can be established between it and other circumstances, in particular treachery. The paper concludes with a pronouncement on whether or not to include the use of weapons in the catalogue of circumstances.